PARADIGMA ASESMEN MULTILITERASI: ANALISIS PRAKTIK FORMATIF, SUMATIF, DAN OTENTIK DI SEKOLAH DASAR - Rofiqi, Ainur; Sari Rufiana, Intan; Rahayuningsih, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of technology and information in the 21st century has changed the literacy landscape. Individuals are required not only to have literacy but also various forms of literacy called multiliteracy. Multiliteracy assessments are necessary to capture the complexity of students' ability to navigate and create meaning in a variety of modes, beyond the limitations of text-based evaluation alone. This study aims to analyze in depth the practice of formative, summative, and authentic assessment in the context of the multiliteracy paradigm in elementary schools, as well as identify challenges in its implementation. The type of research is qualitative with a case study design. The research instrument used interview sheets with data collection techniques through interviews, observations, and document studies. The findings of the study are that the practice of multiliteracy assessment in elementary schools has evolved from simple to complex, including cognitive enhancement, reflective approaches, and multimodality integration. These findings confirm the role of assessment in building multiliteracy comprehensively. The implication is that it is necessary to strengthen teacher competence, adaptive instruments, and the use of technology to optimize implementation.